The Ethics of Space : Homelessness and Squatting in Urban England (2020)
Across the Western world, full membership of society is established through entitlements to space and formalized in the institutions of property and citizenship. Those without such entitlements are deemed less than fully human as they struggle to find a place where they can symbolically and physically exist. Written by an anthropologist who accidentally found herself homeless, The Ethics of Space is an unprecedented account of what happens when homeless people organize to occupy abandoned properties. Set against the backdrop of economic crisis, austerity, and a disintegrating British state, Steph Grohmann tells the story of a flourishing squatter community in the city of Bristol and how it was eventually outlawed by the state. The first ethnography of homelessness done by a researcher who was formally homeless throughout fieldwork, this volume explores the intersection between spatial existence, subjectivity, and ethics. The result is a book that rethinks how ethical views are shaped and constructed through our own spatial existences.